2018
DOI: 10.1021/acs.jmedchem.7b01641
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Metabolic and Renal Clearance in a Series of Indole Acid Direct Activators of 5′-Adenosine Monophosphate-Activated Protein Kinase (AMPK)

Abstract: Optimization of the pharmacokinetic (PK) properties of a series of activators of adenosine monophosphate-activated protein kinase (AMPK) is described. Derivatives of the previously described 5-aryl-indole-3-carboxylic acid clinical candidate (1) were examined with the goal of reducing glucuronidation rate and minimizing renal excretion. Compounds 10 (PF-06679142) and 14 (PF-06685249) exhibited robust activation of AMPK in rat kidneys as well as desirable oral absorption, low plasma clearance, and negligible re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Initial pharmacological evaluation was performed with the human α1β1γ1 AMPK isoform that is predominantly expressed in the kidney, 27,28 and the same assay format was also used to assess isoform selectivity (human α1β2γ1, human α2β1γ1, human α2β2γ1, and human α2β2γ3). Consistent with our previous reports, 21,29 parent carboxylic acids 1−3 potently activate human AMPK isoforms that contained the β1 subunit (including α1β1γ1) (Table 2 and Figure 9). Under these experimental conditions, acyl glucuronide standards of M1, M2, and M3 also selectively activated human β1 isoforms, albeit with 9−19-fold loss in potency (Table 2).…”
Section: Journal Of Medicinal Chemistrysupporting
confidence: 92%
See 2 more Smart Citations
“…Initial pharmacological evaluation was performed with the human α1β1γ1 AMPK isoform that is predominantly expressed in the kidney, 27,28 and the same assay format was also used to assess isoform selectivity (human α1β2γ1, human α2β1γ1, human α2β2γ1, and human α2β2γ3). Consistent with our previous reports, 21,29 parent carboxylic acids 1−3 potently activate human AMPK isoforms that contained the β1 subunit (including α1β1γ1) (Table 2 and Figure 9). Under these experimental conditions, acyl glucuronide standards of M1, M2, and M3 also selectively activated human β1 isoforms, albeit with 9−19-fold loss in potency (Table 2).…”
Section: Journal Of Medicinal Chemistrysupporting
confidence: 92%
“…The present article describes our efforts in the biochemical synthesis, purification, and structural characterization of the glucuronide conjugate of 1 and related analogues PF-06885249 (2) and PF-06679142 (3) (Figure 1) from the indole-3carboxylic acid series of AMPK activators, which have been recently described as potential back-up agents with extended half-lives arising from a net reduction in glucuronidation rates and renal excretion, relative to 1. 29 The biotransformation profile of 2 and 3 in human hepatocytes demonstrated that the predominant route of metabolism also involved glucuronidation (similar to the metabolic fate of 1 in human hepatocytes). Considering the similarities in log D values for 1, 2, and 3, we reasoned that the increased resistance of 2 and 3 toward glucuronidation occurred from a reduction in metabolic rate caused by a diminished affinity for the UGT binding site due to unfavorable active site interactions of the 5-aryl (compound 2) or 4-fluoro (compound 3) substituents rather than a straightforward decrease in lipophilicity.…”
Section: ■ Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…[ 53 ] It further reported PF‐06685249 (EC 50 [AMPKα1γ1β1] = 12.0 nM) ( 10 ), which exhibited robust activation of AMPK in rat kidneys as well as desirable oral absorption. [ 54 ] We previously reported a structure‐based virtual screening based on our “in‐house” compounds library that led to the discovery of compound 17f ( 11 ), which potently activated AMPKα1γ1β1 (EC 50 = 420 nM). [ 55 ] However, compound 17f has insufficient activation capacity as compared with PF‐06409577, which may be related to their different binding modes with AMPK.…”
Section: Introductionmentioning
confidence: 99%
“…5′-Adenosine monophosphate-activated protein kinase (AMPK) is a heterotrimeric serine-threonine kinase (consisting of α-, β-, and γ-subunits) that plays a key role in energy homeostasis. Indole acids 1 , 2 , and 3 (Figure ) were recently identified as potent activators of β1-containing isoforms of AMPK and were evaluated in safety and efficacy studies. In addition, compound 3 was advanced to first-in-human clinical trials as a potential treatment for diabetic nephropathy. The development of improved synthetic routes for producing multigram quantities of 1 and 2 and kilogram quantities of 3 is described herein.…”
Section: Introductionmentioning
confidence: 99%